Four-year prospective study of BMI and mental health problems in young children - Wake, M; Sawyer, M.G.; Sawyer, M; Lynch, J; Harchak, T (My University, 2011)
OBJECTIVE: To investigate prospectively the relationship between BMI and the mental health and health-related quality of life (HRQoL) of young children. METHODS: In this study we used data from the Longitudinal Study of Australian Children obtained when children were 4 to 5 and 8 to 9 years old. BMI was available for 3363 children at both waves. Mental health problems were assessed by using the Strengths and Difficulties Questionnaire (SDQ), which was completed by parents and teachers. HRQoL was assessed by using the Pediatric Quality of Life Inventory (PedsQL), which was completed by the parents. RESULTS: Logistic regression models were adjusted for children's age, gender, baseline SDQ or PedsQL scores, and maternal characteristics. A 1-SD increase in BMI in children aged 4 to 5 years was associated with increased odds of scoring in the abnormal range of the SDQ peer problems scale of 1.15 (95% confidence interval [CI]: 1.03-1.28) for parent reports and 1.20 (95% CI: 1.04-1.37) for teacher reports when these children were aged 8 to 9 years. The odds ratio for children who scored above the at-risk cutoff on the parent-reported PedsQL social problems scale was 1.17 (95% CI: 1.06-1.28) for each 1-SD increase at 4 to 5 years of age. There were also increased odds for teacher reports of childhood emotional problems. CONCLUSIONS: Higher BMI in children aged 4 to 5 years was positively related to poorer peer relationships and teacher-reported emotional problems but not to other childhood mental health problems, in these children at 8 to 9 years of age. Prospective studies are needed to determine if peer problems experienced by children with higher BMI predict subsequent mental health problems in other areas.
Keywords: Health -- Body size, BMI, Body image; Health -- Mental; Families -- Children; Health; Families and relationships; Health and wellbeing; Families; Health; Children; Body size, BMI, Body image; Mental; Health and wellbeing; Families and relationships